PENGARUH GAME ONLINE TERHADAP MINAT BELAJAR SISWA KELAS X SMA N 2 SEMARANG - Silvia Rohmatila Putri; Eny Winaryati (LPPM Universitas Muhammadiyah Muara Bungo, 2025)
Online games are being widely enjoyed by today's teenagers. Online games can have both positive and negative impacts on teenagers. Addiction to online games can affect teenagers' lives at school, one of which is students' interest in learning. Student interest in learning refers to the drive within students to focus attention and energy in learning activities. So this research aims to analyze the influence of online games on the learning interest of class X SMA N 2 Semarang students. The research uses associative research with a quantitative approach. The population in this study were students of SMA 2 Semarang and the sample was 40 class X students. The sampling technique used simple random sampling with survey method data collection techniques, and data processing techniques were carried out using the SPSS application. The results of the analysis show that online games can influence the learning interest of class X SMA N 2 Semarang students significantly and positively (r = 0.636) by 40.5%.